Credit Provision for the Poor: Testing the Theoretical Realm of the Social‐Institutional Basis of the Success of Small‐Scale Financial Institutions in Africa. Issue 2 (June 2016) - Aideyan, Osaore; Omoruyi, Osunde
Abstract : Do creative institutional design and social networks of poverty reduction programs in impoverished countries lower access and transaction costs for the poor and service providers? This question, while important for all impoverished countries, draws particular interest in the African context because there is too much emphasis on whether and why these programs work and not how programs should work in societies that are characterized by uncertainty, hostility to the interests of the poor, and unpredictability in constraining the activities of self‐interested actors. To test whether creative institutional design features and social networks can lead to successful provision of credit to the poor, this article draws on existing records and original rigorous qualitative data on the organizational policies and behavior of borrowers existing in the Lift Above Poverty Organization (LAPO), a national microfinance institution in southern Nigeria, to examine how innovative rules and procedures reduce the access costs faced by the poor for obtaining credit and other services for improved welfare and enhanced productivity. The overall assessment shows that there is a strong relationship between programs, which emphasizes institutional design mechanisms to overcome typical problems of implementing programs that benefit the poor.